FIKIH PERLINDUNGAN ANAK DALAM KELUARGA DI ERA PERDAGANGAN BEBAS - Abdulahanaa, Abdulahanaa (Institut Agama Islam Negeri Bone, 2022)
In the eyes of Islamic law (fikih) the future of child education require to get the special attention. Children is inclusive of faction’s man that straw from all aspect. Therefore, protection and construction passed to exceed the protection to adult. Law sanction given to one who conduct the badness to child at era of free trade have to be adapted for a modus character act the criminal expanding, so that earn effective prevent the disservice of future of child education. When needed law sanction given by earn the heavy penalization, considering weak children condition, so that ought to more protected In principle in Islamic law ( fikih) have been arranged by a special law for children, good concerning penalization which is passed to arsonist to child, and also penalization given to naughty child. Principal specialty punish for child is for the shake of taking care of education future and its prosperity as heir of responsibility of religion router, nation and state. Any conducted by children basically not yet been incured by the burden punish.